2012
DOI: 10.1136/ejhpharm-2011-000027
|View full text |Cite
|
Sign up to set email alerts
|

Stability of dobutamine 500 mg in 50 ml syringes prepared using a Central Intravenous Additive Service

Abstract: Objectives A pharmacy Central Intravenous Additives Service (CIVAS) provides ready to use injectable medicines. However, manipulation of a licensed injectable medicine may signifi cantly alter the stability of drug(s) in the fi nal product. The aim of this study was to develop a stability indicating assay for CIVAS produced dobutamine 500 mg in 50 ml dextrose 1% (w/v) prefi lled syringes, and to allocate a suitable shelf life. Methods A stability indicating high performance liquid chromatography (HPLC) assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…No loss in the concentration of dobutamine or appearance of degradation peaks could be observed after exposure of dobutamine solution to 0.5 mol/L hydrochloric acid for 72 hours. Our findings are consistent with the result reported by Patel et al 9 They stressed dobutamine in the presence of 0.1, 1 or 2 mol/L HCl for 72 hours and reported no degradation of dobutamine. The observed degradation products did not interfere with the peak of dobutamine, suggesting the developed HPLC method is capable of investigating the chemical stability of dobutamine.…”
Section: Stability-indicating Capability Of the Newly Developed Hplsupporting
confidence: 94%
See 1 more Smart Citation
“…No loss in the concentration of dobutamine or appearance of degradation peaks could be observed after exposure of dobutamine solution to 0.5 mol/L hydrochloric acid for 72 hours. Our findings are consistent with the result reported by Patel et al 9 They stressed dobutamine in the presence of 0.1, 1 or 2 mol/L HCl for 72 hours and reported no degradation of dobutamine. The observed degradation products did not interfere with the peak of dobutamine, suggesting the developed HPLC method is capable of investigating the chemical stability of dobutamine.…”
Section: Stability-indicating Capability Of the Newly Developed Hplsupporting
confidence: 94%
“…8 The stability of dobutamine in various fluids and containers has been investigated before. For example, Patel et al 9 for 24 hours. Also, dobutamine is known to be stable for 48 hours when mixed with large volume parenteral solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to light is thought to be one of the dominating stability factors [14,15,22], however in our study differentiation in the stability of inotropes in varying dilution vehicles was not seen at location A after 24 hours. More importantly we did not observe any significant differences in the concentration of dopamine in 0.9 % NaCl at location A and B after 24 hours in clear and orange tubing (utilised to present light).…”
Section: Differences In the Stability Of Inotropes Following 24-hour contrasting
confidence: 79%
“…One potential explanation of this observation is due to the stability of the drug. There are a limited number of studies conducted on the stability of dopamine and dobutamine which have found that light and temperature appear to be dominating factors for influencing stability [11][12][13][14][15][16]. However, most these studies have not been conducted on clinical doses and in environments that match ward settings.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for the analyses of this compound, such as spectrophotometric assay [6] , pH metric determination [7] , chemiluminescence [8] , HPLC assay with fluorimetric, electrochemical and UV detection [9] , [10] , [11] , [12] , [13] , [14] and solid phase extraction method [15] .The present paper reports on the development of a new, validated, fast and sensitive method by using HPLC with PDA detection for the quantitative determination of DBT in rat plasma. Compared with old methods this is more sensitive, rapid and validated at very low level of quality control (QC) samples.…”
Section: Introductionmentioning
confidence: 99%